A View on Bley-Vroman’s Fundamental Characters of Foreign Language Learning in Indonesian High Schools - Abidah, Sa'wanatul (Lingual Journal of Language and Culture; Vol 3 No 1 (2017)DO - 10.24843/LJLC.2017.v03.i01.p04, 2017)
English as a subject has  been a part of curriculum in Indonesian schools from primary to university study for several decades now. The decision of education authorities to include it as a compulsory subject in high school is based on the fact that English has played an important  role as academic language that is universally used, as well as the belief that having good English proficiency will enable Indonesian young people to face the fierce competition in global world. However, this policy does not run without challenge. Problems  in mastering the language are encountered by both teachers and students, and results of the learning are not always as expected. This is a signature of foreign language learning as elaborated by Vroman in his book (The Logical Problem of Foreign Language  Learning). This paper reviews on how the characters of language learning proposed by Vroman are seen in Indonesian classrooms at high school level where English is learned as a foreign language. Keywords: English, foreign language, Indonesian high schools.